PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI FOLLOWERS INSTAGRAM BATIK ELLYDA STORE - Risang Galuh Sekartaji; Wagiyem Wagiyem (STIE Atma Bhakti, 2022)
Nowadays, many fashion businesses have sprung up that use social media accounts to market their products, so that the fashion business competition becomes tougher. Therefore, fashion business people are required to be more creative, innovative and able to maximize the use of social media as a marketing medium. Fashion business actors must pay attention to the use of social media in accordance with their target market so that the message given is effective, efficient and meets the purpose of its use. This study aims to determine the effect of social media marketing Instagram on buying interest in Instagram followers @batik_ellydastore. This research uses quantitative methods. The sample collection technique used purposive sampling. Data collection was carried out by distributing questionnaires online via google form to as many as 63 respondents. The results showed that partially the context, communication, collaboration and connection variables had a significant effect on buying interest.